Inching closer to realistic exposure models. Issue 11 (November 2018) - Lowry, Gregory
Engineered nanomaterials are often highly reactive and readily transform to new species. New modelling capabilities incorporate these transformations into estimates of environmental exposure concentrations and associated risks more accurately.